Republic of Bulgaria : Institutional Fiduciary Assessment (IFA) of Road Executive Agency - World Bank (Washington, DC, 2012)
This Institutional Fiduciary Assessment (IFA) of the Road Executive Agency (REA) was commissioned by the World Bank (WB) country and infrastructure sector management in connection with the government's request to provide the World Bank financing for a new Road Infrastructure Project (project). The IFA was used as a tool to assess the performance of the REA in regard to the financial management and procurement systems in order identify the areas in REA's public finance management that can be further strengthened to improve utilization of public funds irrespective of the source of financing. The Government wants to improve the condition of class two and three roads so as to enhance the population's access to markets and enterprises in small towns and rural areas and enhance business opportunities in rural areas expected after the EU accession. Second, REA wants to improve its road management system in order to be able to prepare multiyear road maintenance programs under a constrained budget environment. Third, the Government wants REA to strengthen its technical and managerial capacity to efficiently implement ongoing and future road projects, especially those to be partly financed with EU grants. This section presents a summary table of fiduciary issues and risks attached to the financial management and procurement arrangements in connection with REA's re-organization into an extra-budgetary fund responsible for the national road network, including new construction and maintenance. The list of issues identified by the World Bank fiduciary team during field work from May to early June 2006 is by no means considered exhaustive. The team was not provided full access to all the required information and documents, thus, only enabling the team to assess REA's internal control framework at a very general level without the possibility of checking the application of the control in practice. Therefore, the IFA report presents only limited observations, findings and recommendations based on interviews and meetings both at REA and other relevant institutions listed. The report does not provide a detailed action plan but identifies the areas to be looked at more closely, including with the help of additional technical assistance.